Strategy Formulating Based On Critical Success Factors In Mutiara Bakery MSMES - Budi UTAMI; Sudarmiatin SUDARMIATIN; Agus HERMAWAN (International Journal of Environmental, Sustainability, and Social Science, 2022)
Mutiara Bakery is a UMKM that produces and markets bread. Currently, only 2 (two) stores are operating. CPM is an appropriate strategic management tool in identifying the strengths and weaknesses of the main competitors in relation to the strategic position of the products or services offered. This research aims to strategy formulating based on critical success factors in Mutiara bakery MSMEs. The basic method used in this research is the descriptive-analytical method. The technical implementation of this research is carried out using a survey technique, namely the method of collecting data from a number of units or individuals at the same time (or period). The results showed that Mutiara Bakery SMEs needed. The proposed marketing strategy can be divided into 2 groups, short-term and long-term. The short term can be done now, while the long term is done after waiting for capital input. Strategies that can be carried out by MSME Mutiara Bakery can now be seen as follows: 1. Creating new, more attractive packaging designs 2. Sales are made online using Facebook, Instagram, and WhatsApp.